THE LEVEL OF DANGER IN CONTROLLED AIRPORT SECURITY (Transport systems and technologies, 2021)
The functionality of the aircraft complex is determined by quality and safety. This is defined by the relationship between the entities airport – aircraft – airspace. Operational safe management and control at the airport is a directed action of independent factors. Their expression is embedded in the feeling of security and safety of each air traffic participant. Fulfilment of the ethical characteristics of security requires the implementation of management so that the control at the airport is carried out in the relevant security zone. Construction of a safe state can be achieved if the chosen method of safety experiments will faithfully reflect the real error in the control of air transport. The correctness of safety control procedures can be verified by simulation and models built on a physical basis. The motive of the article is to show one way of effective identification of errors in the management of security controls actors of air transport.
Keywords: airport, security, control system, probability, sensitivity, danger .